Programmed cell death‐1 3′‐untranslated region polymorphism is associated with spontaneous clearance of hepatitis B virus infection. Issue 11 (13th August 2018) - Chihab, Hajar; Jadid, Fatima‐Zahra; Foka, Pelagia; Zaidane, Imane; El Fihry, Raouia; Georgopoulou, Urania; Marchio, Agnes; Elhabazi, Abdellah; Chair, Mohammed; Pineau, Pascal; Ezzikouri, Sayeh; Benjelloun, Soumaya
Abstract : Hepatitis B virus (HBV)‐specific CD8+ T cells play an important role in the clearance of HBV infection. Programmed cell death‐1 (PD‐1), an immunosuppressive molecule that regulates T‐cell activation and peripheral immune tolerance, is increasingly shown to influence the outcome of HBV infection. rs10204525, a single‐nucleotide polymorphism in the 3′‐untranslated region (3′‐UTR) of PD‐1, has been associated with susceptibility and disease progression of chronic HBV infection in far‐eastern patients. The aim of our study was to assess the impact of rs10204525 variation on HBV infection in Moroccan patients. A total of 236 patients with chronic HBV infection and 134 individuals with spontaneous HBV resolution were genotyped using a Taqman assay. In addition, PD‐1 mRNA expression in peripheral blood nuclear cells was determined by quantitative reverse‐transcription polymerase chain reaction. We found that the AA genotype is protective (odds ratio, 0.43; 95% confidence interval, 0.19 to 0.97; P = 0.038) against HBV infection. Interestingly, PD‐1 messenger RNA (mRNA) expression analysis has revealed that chronic HBV carriers with GG and GA displayed higher levels of PD‐1 mRNA compared with corresponding genotypes in resolved subjects ( P = 0.031 and 0.014, respectively). Our data suggest that Mediterranean HBV‐infected patients carrying PD‐1 GG and GA genotypes at rs10204525 have high PD‐1 mRNA expression and may be more prone to installation of chronicity.